An Examination of the Four-Part Theory of the Chinese Self: The Differentiation and Relative Importance of the Different Types of Social-Oriented Self - Sun, Chien-Ru (Frontiers in Psychology, 2017)
Because culture has a deep and far-reaching influence, individuals who grew up within different cultures tend to develop different basic self-constructions. With respect to the Chinese under the influence of Chinese culture, Yang proposed the concepts of individual-oriented self and social-oriented self. He argued that, besides the individual-oriented self, the social-oriented self of the Chinese contains three types of self: the relationship-oriented self, the familistic (group)-oriented self, and the other-oriented self. The theory proposed that the Chinese self is appropriately covered only through this four-part theory of the Chinese self. However, this remains to be tested; whether these three types of sub-level “selves” can be effectively triggered, along with their relative importance. This study examines the four-part theory of the Chinese self. Through photo priming, Experiment 1 shows that the three types of social-oriented self are differentiated from each other and can be individually triggered. In Experiment 2, the importance of the three types of self was investigated, adopting the concept of limited self-regulation resources to design scenarios. The participants were asked to make counterarguments about the notion of each of the three types of self, with performance in the subsequent task serving as the main dependent variable. In Experiment 3, the relative importance of the three types of self was examined by investigating the choices made by individuals within the context of conflict under the three orientations of the social-oriented self. Overall, results of the experiments showed that the Chinese have a four-part self with the importance of the other-oriented self as the most remarkable.